Using a Non-Traditional Method in Teaching Drawing Geometry - Tanjarova, R. A.; Mambetov, R. M.; Dosmetov, S. G. (International Journal on Orange Technologies, 2023)
This article describes an example of one subject using a non-traditional method of teaching the science of drawing geometry. Tests were also created without leaving the selected subject and the possibilities of providing students with in-depth knowledge based on this subject were identified.